Mutation-based, neoadjuvant treatment for advanced anaplastic thyroid carcinoma - Wächter, Sabine; Bartsch, Detlef K.; Knorrenschild, J. Riera; Pehl, Anika; Eilsberger, Friederike; Pfestroff, Andreas; Luster, Markus; Holzer, Katharina; Neubauer, Andreas; Maurer, Elisabeth (Frontiers in Endocrinology, 2025)
IntroductionThe prognosis of anaplastic thyroid carcinoma (ATC) remains poor. Mutation-based targeted therapies and immune checkpoint inhibitors (ICI) have gained increasing importance in the treatment of advanced tumor stages. This study aimed to investigate whether mutation-based neoadjuvant therapy can convert an initially unresectable tumor into a resectable state, optimizing local tumor control and prolonging overall survival.MethodsPatients with stages IVB and limited IVC BRAFV600E-negative ATC received immediate combination therapy consisting of the multikinase inhibitor (mKI) lenvatinib and the immune checkpoint inhibitor (ICI) pembrolizumab upon diagnosis. Patients with BRAFV600E-positive tumors were treated with a BRAF/MEK inhibitor regimen, consisting of dabrafenib and trametinib. This neoadjuvant therapy was administered for 4–6 weeks before re-staging. If FDG-PET/CT imaging demonstrated tumor regression, surgical resection of the primary tumor was performed. In cases of limited distant metastases, these were also surgically removed. In the adjuvant setting, mutation-based systemic therapy was continued.ResultsBetween December 2021 and December 2024, a total of 14 patients were screened. Ultimately, 12 patients, with a median age of 73 years (range: 54–85), were treated with neoadjuvant therapy. At diagnosis, six patients had UICC stage IVB and six stage IVC ATC. A BRAFV600E-mutation was detected in two patients. Following neoadjuvant therapy, eight patients showed tumor regression, whereas three exhibited an inadequate response, characterized by disease progression or a mixed response on FDG-PET/CT. In one patient, therapy was discontinued early due to severe local symptoms. During neoadjuvant treatment, two cases of tracheoesophageal or tracheocutaneous fistulas were observed. Surgical resection was performed in nine patients. An R0 resection was achieved in two, an R1 resection in six, and an R2 resection in one patient. The median follow-up period was eight months (range 1–36). Median progression-free survival (PFS) was three months (range 1–not reached), while median overall survival (OS) was nine months (range 1–not reached).ConclusionNeoadjuvant therapy for advanced ATC appears to be a promising treatment approach for a subset of affected patients. While initial results are encouraging, further research is needed to establish its precise role within the multimodal management of this aggressive malignancy.